Copper-Catalyzed Negishi Coupling of Diarylzinc Reagents with Aryl Iodides - Thapa, Surendra; Vangala, Adarsh S.; Giri, Ramesh (Synthesis, 2016)
We report an efficient copper(I) iodide catalyzed cross-coupling of diarylzinc reagents with aryl iodides. The reaction proceeds under ligand-free conditions at low catalyst loading (5 mol%) and tolerates a variety of functional groups.
Keywords: copper; cross-coupling; diarylzinc; ligand-free; Negishi coupling